UVCB substances II: Development of an endpoint‐nonspecific procedure for selection of computationally generated representative constituents. (18th February 2019) - Kutsarova, Stela S.; Yordanova, Darina G.; Karakolev, Yordan H.; Stoeva, Stoyanka; Comber, Mike; Hughes, Christopher B.; Vaiopoulou, Eleni; Dimitrov, Sabcho D.; Mekenyan, Ovanes G.
Abstract: Substances of unknown or variable composition, complex reaction products, and biological materials (UVCBs) comprise approximately 40% of all registered substances submitted to the European Chemicals Agency. One of the main characteristics of UVCBs is that they have no unique representation. Industry scientists who are part of the scientific community have been working with academics and consultants to address the problem of a lack of a defined structural description. It has been acknowledged that one of the obstacles is the large number of possible structural isomers. We have recently proposed and published a methodology, based on the generic substance identifiers, to address this issue. The methodology allows for the coding of constituents, their generation, calculation of important characteristics of UVCB constituents, and selection of representative constituents. In the present study we introduce a statistical selection of the minimum number of generated constituents representing a UVCB. This representative sample was selected in such a way that the structural variability and the properties of concern of the UVCB were approximated within a predefined tolerable error. The aim of the statistical selection was to enable the assessment of UVCB substances by decreasing the number of constituents that need to be evaluated. The procedure, which was shown to be endpoint‐independent, was validated theoretically and on real case studies. Environ Toxicol Chem 2019;38:682–694. © 2019 SETAC